Interplay between postcranial morphology and locomotor types in Neotropical sigmodontine rodents - Carrizo, Luz V (John Wiley & Sons Ltd, 2014)
Sigmodontine rats are one of the most diverse components of the Neotropical mammal fauna. They exhibit a wide ecological diversity and a variety of locomotor types that allow them to occupy different environments. To explore the relationship between morphology and locomotor types, we analyzed traits of the postcranial osteology (axial and appendicular skeletons) of 329 specimens belonging to 51 species and 29 genera of sigmodontines exhibiting different locomotor types. In this work, postcranial skeletal characters of these rats are considered in an ecomorphological study for the first time. Statistical analyses showed that of the 34 osteological characters considered, 15 were related to the locomotor types studied, except for ambulatory. However, character mapping showed that climbing and jumping sigmodontines are the only taxa exhibiting clear adaptations in their postcranial osteology, which are highly consistent with the tendencies described in many other mammal taxa. Climbing, digging and swimming rats presented statistically differences in traits associated with their vertebral column and limbs, whereas jumping rats showed modifications associated with all the skeletal regions. Our data suggest that sigmodontine rats retain an all-purpose morphology that allows them to use a variety of habitats. This versatility is particularly important when considering the lack of specialization of sigmodontines for a specific locomotor mode. Another possible interpretation is that our dataset probably did not consider relevant information about these groups and should be increased with other types of characters (e.g. characters from the external morphology, myology, etc.).